On both sides of the quality bias in price indexes - Bart Hobijn (Federal Reserve Bank of New York, 2002)
It is often argued that price indexes do not fully capture the quality improvements of new goods in the market. Because of this shortcoming, price indexes are perceived to overestimate the actual price increases that occur. In this paper, I argue that the quality bias in price indexes is just as likely to be upward as it is to be downward. I show how both the sign and the magnitude of the quality bias in the most commonly applied price index methods are determined by the cross-sectional variation of prices per quality unit across the product models sold in the market. I do so by simulating a model of a market that includes monopolistically competing suppliers of the various product models and a representative consumer with CES (constant elasticity of substitution) preferences. I illustrate the bias in the commonly applied price index methods by comparing their estimates of inflation with the theoretical inflation rate implied by the data-generating process.
Keywords: C43; D11; D43; L13; 330; Price index theory; hedonic price methods; quality bias; monopolistic competition; Preisindex; Produktqualität; Monopolistischer Wettbewerb; Hedonischer Preisindex; Simulation; Theorie